Fissured firms and worker outcomes - Guido Matias Cortes; Diego Dabed; Ana Oliveira; Anna Salomons (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We consider how firms' organization of production relates to workers' wages. Using matched employer-employee data from Portugal, we document that firms differ starkly in their occupational employment concentration, even within detailed industries, with some firms employing workers across a broad range of occupations and others being much more specialized. These differences are robustly predictive of wages: a worker employed in a specialized, i.e. "fissured" firm, earns less than that same worker employed in a less specialized firm. This wage penalty for working in a fissured firm is observed across occupations of all skill levels. Firm specialization helps account for the role of firms in inequality, as specialization is strongly negatively related to estimated AKM firm fixed effects. Around two-thirds of the wage penalty from fissuring is explained by differences in firm productivity. Fissured firms also engage in lower rates of rent-sharing conditional on productivity, accounting for around one-quarter of the difference in wage premia between high- and low-specialization firms. Finally, we show that being employed in a specialized firm is also associated with worse longer-term career outcomes for workers.
Keywords: J24; J31; 330; Occupational Segregation; Between-Firm Wage Inequality; Firm Productivity; Rent-Sharing